1

Jika f x = 2 x + 3 , x 1 2 x + 1 x - 2 , x < 1 maka lim x 1 f x =

a. 5

b. - 3

c. 3

d. tidak terdefinisi

Lihat Penyelesaian

2

Pada gambar di bawah ini, pernyataan yang salah adalah …

a. lim x 10 + f x = 9

b. lim x 4 f x = 6

c. lim x 10 f x = 13

d. lim x 4 - f x = 6

Lihat Penyelesaian

3

lim x 2 2 x 2 + x - 1 =

a. 9

b. 17

c. 11

d. tidak terdefinisi

Lihat Penyelesaian

4

lim x 0 x 2 - 2 x x =

a. 1

b. - 2

c. 0

d. tidak terdefinisi

Lihat Penyelesaian

5

lim x - 1 x + 5 x - 1 =

a. - 2

b. 4

c. 3

d. tidak terdefinisi

Lihat Penyelesaian

6

lim x x 2 - 2 x x =

a. 1

b. - 2

c. 0

d. tidak terdefinisi

Lihat Penyelesaian

7

lim x x 2 + 2 x x 2 - x =

a. - 2

b. 1

c. - 1

d. tidak terdefinisi

Lihat Penyelesaian

8

lim x 0 sin 3 x x =

a. 0

b. 3

c. 1

d. 9

Lihat Penyelesaian

9

lim x 0 x cos 2 x =

a. 0

b. 1 4

c. 1 2

d. 1

Lihat Penyelesaian

10

f x = x 2 + 2 x - 3 akan diskontinu di x =

a. - 3

b. - 2 3

c. 3

d. 2 3

Lihat Penyelesaian